2022
DOI: 10.1111/pbi.13939
|View full text |Cite
|
Sign up to set email alerts
|

SPINDLY interacts with EIN2 to facilitate ethylene signalling‐mediated fruit ripening in tomato

Abstract: The post-translational modification of proteins enables cells to respond promptly to dynamic stimuli by controlling protein functions. In higher plants, SPINDLY (SPY) and SECRET AGENT (SEC) are two prominent O-glycosylation enzymes that have both unique and overlapping roles; however, the effects of their O-glycosylation on fruit ripening and the underlying mechanisms remain largely unknown. Here we report that SlSPY affects tomato fruit ripening. Using slspy mutants and two SlSPY-OE lines, we provide biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Fifteen TOR-regulated phosphoproteins are both O -fucosylated and O -GlcNAcylated ( Fig. 4A ; Supplemental Dataset S8 ), including EIN2, a key component of the ethylene signaling pathway recently reported to be a substrate of TOR ( Fu et al 2021 ) and to interact with SPY in tomato ( Solanum lycopersicum ) ( Xu et al 2022 ). Almost half of the O -GlcNAcylated proteins (128 of 262) are O -fucosylated.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen TOR-regulated phosphoproteins are both O -fucosylated and O -GlcNAcylated ( Fig. 4A ; Supplemental Dataset S8 ), including EIN2, a key component of the ethylene signaling pathway recently reported to be a substrate of TOR ( Fu et al 2021 ) and to interact with SPY in tomato ( Solanum lycopersicum ) ( Xu et al 2022 ). Almost half of the O -GlcNAcylated proteins (128 of 262) are O -fucosylated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that posttranslational modifications also play a role in fruit ripening. For instance, a recent report observed SPINDLY (O-glycosylation enzymes) collaborated with EIN2 to enhance the process of ET signaling, which in turn promoted the ripening of fruits in S. lycopersicum plants [103]. Histone modifiers, like histone deacetylases, are enlisted by AP2/ERFs to regulate fruit ripening.…”
Section: Fruit Ripeningmentioning
confidence: 99%